Comparative evaluation of the efficacy of 1% and 3% Sodium hypochlorite in reducing the microbial counts in primary teeth root canals using Bioluminometer - A randomized clinical trial - Divya Mukundan; Ganesh Jeevanandan; Satish Vishwanathaiah; Suman Panda; Tazeen Dawood; Aseel Abutaleb; Prabhadevi C. Maganur (Elsevier, 2024)
Purpose: Sodium hypochlorite (NaOCl) is commonly used to irrigate primary teeth during pulpectomy. Although high concentrations of NaOCl are effective, they pose a risk of toxic damage to periapical tissues if NaOCl penetrates through the apical foramen. Therefore, low concentrations of NaOCl are preferred to mitigate this risk. However, concerns persist regarding the antibacterial efficacy of low concentrations of NaOCl compared to high concentrations. The objective of this study was to assess and compare the efficacy of 1% and 3% NaOCl irrigation in reducing bacterial load within primary teeth root canals. Materials and methods: This clinical study involved forty participants divided into two groups. Group 1 (n = 20) received canal irrigation with 1 % NaOCl solution, while Group 2 (n = 20) received canal irrigation with 3 % NaOCl solution. Microbial samples were collected from the root canal using a paper point before and after irrigation. The samples were aseptically transferred to ultra-snap tubes and then analyzed using a Bioluminometer. The results were recorded. Results: Both groups exhibited a decrease in bacterial count after irrigation. The mean colony count post irrigation for 3 % NaOCl was 258.05 ± 28.61, and for 1 % NaOCl it was 267.60 ± 30.56. However, no statistically significant difference was observed upon intergroup comparison. Conclusion: This study shows that 1% NaOCl is equally effective as 3% NaOCl in reducing bacterial count in root canals. Thus, using 1% NaOCl as an irrigant is appropriate in clinical practice.